2007
DOI: 10.1063/1.2718286
|View full text |Cite
|
Sign up to set email alerts
|

New criterion of glass forming ability for bulk metallic glasses

Abstract: It has been confirmed that glass-forming ability ͑GFA͒ is related to not only liquid phase stability but also the crystallization resistance. In this study, it was found the liquidus temperature T l and supercooled liquid region T x − T g could reflect the stability of glass-forming liquids at the equilibrium and undercooled state, respectively, while the onset crystallization temperature T x could indicate the crystallization resistance during glass formation. Thus, a modified ␥ parameter, defined as ␥ m = ͑2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 29 publications
2
83
0
2
Order By: Relevance
“…10 On the one hand, according to FVM, the smaller free volume of liquid results in higher liquid viscosity 8,9 and therefore lower atomic mobility, as well as the more stabilized liquid phase. [1][2][3][4][5][6][7][21][22][23] On the other hand, the glass forming liquid with a smaller free volume has a smaller entropy of fusion and consequently smaller gradient in DG (Gibbs free energy difference between the super-cooled liquid and the crystal) at the melting point, which results in a lower driving force for crystallization and therefore a greater GFA. 3,4,22 In short, the viscosity and DG, the two dominant factors of GFA, are related to each other via the free volume of liquid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 On the one hand, according to FVM, the smaller free volume of liquid results in higher liquid viscosity 8,9 and therefore lower atomic mobility, as well as the more stabilized liquid phase. [1][2][3][4][5][6][7][21][22][23] On the other hand, the glass forming liquid with a smaller free volume has a smaller entropy of fusion and consequently smaller gradient in DG (Gibbs free energy difference between the super-cooled liquid and the crystal) at the melting point, which results in a lower driving force for crystallization and therefore a greater GFA. 3,4,22 In short, the viscosity and DG, the two dominant factors of GFA, are related to each other via the free volume of liquid.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] A glass forming liquid or amorphous solid with higher density compared to their crystalline counterpart is found to have higher GFA. 6,7 This phenomenon can be explained by Cohen and Turnbull's free volume model (FVM).…”
Section: Introductionmentioning
confidence: 99%
“…For multicomponent metallic glasses the measure of  has been reported to be more accurate than T rg [17]. To improve this  parameter, Du et al had also considered T x in addition of T x and T l and proposed  m [18].…”
Section: Resultsmentioning
confidence: 99%
“…The most widely used indicators are T rg , DT x , and c. In a recent work, Guo et al 10 evaluated these criteria using statistical and physical considerations and found the best indicator of the GFA for the c m criterion. 5 The biggest short coming, however, is that they cannot predict new compositions, since they make use of thermal properties of the glassy state. Therefore, the forecast of GFA is impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters to evaluate the glass-forming ability (GFA) have been proposed over the years based on thermal behavior, such as T rg (¼ T g /T l ), 1 5 /[¼ T rg (DT x /T g ) 0.143 ], 6 b[¼ T x T g /(T l ÀT x ) 2 ], 7 a(¼ T x /T l ) 8 and x[¼ T g /T x À2T g /(T g þT l )], 9 where T x , T l , and T g are the onset crystallization, liquidus and glass transition temperatures, respectively. The most widely used indicators are T rg , DT x , and c. In a recent work, Guo et al 10 evaluated these criteria using statistical and physical considerations and found the best indicator of the GFA for the c m criterion.…”
Section: Introductionmentioning
confidence: 99%